Human Adipose- and Amnion-Derived Mesenchymal Stromal Cells Similarly Mitigate Osteoarthritis Progression in the Dunkin Hartley Guinea Pig. Issue 14 (December 2022) - Kwapisz, Adam; Bowman, Mackenzie; Walters, Joshua; Cosh, Heather; Burnikel, Brian; Tokish, John; Ye, Tong; Mercuri, Jeremy
Background: Clinical trials are currently underway to investigate the efficacy of intra-articular administration of mesenchymal stromal cells (MSCs) to mitigate osteoarthritis (OA) progression in the knee. Although multiple MSC sources exist, studies have yet to determine whether differences in therapeutic efficacy exist between them. Purpose: To compare the ability of intra-articularly injected adipose-derived MSCs (AD-MSCs) and amnion-derived MSCs (AM-MSCs) to mitigate the progression of knee OA in a small animal model of spontaneous OA, as well as to compare the therapeutic potential of MSCs in hyaluronic acid (HA) and in HA only with saline (OA) controls. Study Design: Controlled laboratory study. Methods: Injections of AD-MSCs or AM-MSCs suspended in HA or HA only were performed in the rear stifle joints of 3-month-old Dunkin Hartley guinea pigs (DHGPs). Repeat injections occurred at 2 and 4 months after the initial injection in each animal. Contralateral limbs received saline injections and served as untreated controls. Subsequently, joints were analyzed for osteoarthritic changes of the cartilage and subchondral bone via histologic and biochemical analyses. To evaluate MSC retention time in the joint space, DHGPs received a single intra-articular injection of fluorescently labeled AD-MSCs or AM-MSCs, and the fluorescence intensity was longitudinally tracked via an in vivo imaging system. Results: No statistically significant differences in outcomes were found when comparing the ability of AD-MSCs and AM-MSCs to mitigate OA. However, the injection of AD-MSCs, AM-MSCs, and HA-only treatments more effectively mitigated cartilage damage compared with that of saline controls by demonstrating higher amounts of cartilage glycosaminoglycan content and improved histological proteoglycan scoring while reducing the percentage of osteophytes present. Conclusion: Intra-articular injection of AD-MSCs, AM-MSCs, or HA only was able to similarly mitigate the progression of cartilage damage and reduce the percentage of osteophytes compared with that of saline controls in the DHGP. However, this study was unable to establish the superiority of AD-MSCs versus AM-MSCs as a treatment to mitigate spontaneous OA. Clinical Relevance: MSCs demonstrate the ability to mitigate the progression of knee OA and thus may be used in a prophylactic approach to delay the need for end-stage treatment strategies.